2020
DOI: 10.3390/diagnostics10090635
|View full text |Cite
|
Sign up to set email alerts
|

Could Galectin 3 Be a Good Prognostic Factor in Endometrial Cancer?

Abstract: Galectin 3 is a modulator of several basic biological functions. It may be involved in the development of obesity and type 2 diabetes—risk factors of endometrial cancer. The study involved 144 patients, after abrasion due to postmenopausal bleeding. Galectin 3 concentrations were quantified in serum by multiplex fluorescent bead-based immunoassays. Median serum galectin 3 concentrations revealed significant differences between FIGO III and IV vs. FIGO I and II patients. Statistically higher concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Simultaneously, tumors produce large amounts of galectins (mainly galectins -1, -3, -7, -8, and -9). As already stated, increased levels of galectins in patients' sera have been reported for several cancer types [27][28][29][30][31][32][33][34][35][36][37][38]. In such conditions of abundant production and secretion, galectins circulate through biological fluids and reach the thymus.…”
Section: Do Circulating Tumor-derived Galectins Have Any Impact On Naïve T Cell Production?mentioning
confidence: 96%
See 1 more Smart Citation
“…Simultaneously, tumors produce large amounts of galectins (mainly galectins -1, -3, -7, -8, and -9). As already stated, increased levels of galectins in patients' sera have been reported for several cancer types [27][28][29][30][31][32][33][34][35][36][37][38]. In such conditions of abundant production and secretion, galectins circulate through biological fluids and reach the thymus.…”
Section: Do Circulating Tumor-derived Galectins Have Any Impact On Naïve T Cell Production?mentioning
confidence: 96%
“…As a consequence, increased levels of these galectins are detected in the sera of cancer patients. Until mid-2021, more than 55 independent studies have been recorded in this field (here, and due to space limitations, we only cite some examples on each galectin member [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]).…”
Section: Introductionmentioning
confidence: 99%
“…However, contradictory results from a study involving 144 patients showed that increased galectin 3 expression was observed in patients with lymphovascular space invasion ( Cymbaluk-Ploska., et al, 2020 ). The mean scores progressively increased from normal endometria (2.58) and atypical hyperplasia (4.77) to clear cell carcinoma (6.71), and significant differences were noted among the various conditions.…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…Its concentration strictly correlated with the degree of tumor advancement [ 16 ]. A recent study [ 34 ] analyzed the clinical implications of galactin-3 in patients with endometrial cancer. Apart from the higher galectin-3 levels in EC patients compared to normal endometrium, significantly higher values of galectin-3 levels were found in patients with obesity, type 2 diabetes and increased levels of C-reactive protein and in nulliparous vs. multiparous women.…”
Section: Adipokinesmentioning
confidence: 99%